2015
DOI: 10.1039/c5nr00166h
|View full text |Cite
|
Sign up to set email alerts
|

Dual-protection of a graphene-sulfur composite by a compact graphene skin and an atomic layer deposited oxide coating for a lithium-sulfur battery

Abstract: A reduced graphene oxide (rGO)-sulfur composite aerogel with a compact self-assembled rGO skin was further modified by an atomic layer deposition (ALD) of ZnO or MgO layer, and used as a free-standing electrode material of a lithium-sulfur (Li-S) battery. The rGO skin and ALD-oxide coating worked as natural and artificial barriers to constrain the polysulfides within the cathode region. As a result, the Li-S battery based on this electrode material exhibited superior cycling stability, good rate capability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 48 publications
1
59
0
Order By: Relevance
“…[16][17][18][19][20] Shi et al 27 synthesized a binder-free reduced graphene oxide-sulfur composite aerogel with a self-assembled compact reduced graphene oxide skin by hydrothermal method, showing an initial discharge capacity of 796 mAh g −1 and capacity retention of 81% after 250 cycles. Yang et al 28 reported electrochemical assembly strategy to achieve ordered sulfur-graphene nanowalls. Inspired by the effective electrolytic exfoliation of graphite into graphene aggregates recently reported, 29−32 herein, we report a facile and novel strategy to synthesis graphene-sulfur composites (GSC) basing on a rational design of electrolytic exfoliation of graphite into graphene combined with in situ electrodeposition of sulfur as a one-pot reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19][20] Shi et al 27 synthesized a binder-free reduced graphene oxide-sulfur composite aerogel with a self-assembled compact reduced graphene oxide skin by hydrothermal method, showing an initial discharge capacity of 796 mAh g −1 and capacity retention of 81% after 250 cycles. Yang et al 28 reported electrochemical assembly strategy to achieve ordered sulfur-graphene nanowalls. Inspired by the effective electrolytic exfoliation of graphite into graphene aggregates recently reported, 29−32 herein, we report a facile and novel strategy to synthesis graphene-sulfur composites (GSC) basing on a rational design of electrolytic exfoliation of graphite into graphene combined with in situ electrodeposition of sulfur as a one-pot reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Such improved rate capability and cycle stability are attributed to the unique coaxial architecture of the nanocomposite, in which graphene and CNFs enable electrodes with improved electrical conductivity, better ability to trap soluble polysulfide intermediates and accommodate volume expansion/shrinkage of sulfur during cycling [68]. Gao et al reported a reduced graphene oxide-sulfur composite aerogel with a compact self-assembled graphene oxide skin as cathode materials for Li-S batteries [69]. This electrode was further modified by an atomic layer deposition of ZnO or MgO for a free-standing electrode to prevent the polysulfide shuttle (Fig.…”
Section: Carbon-sulfur Compositesmentioning
confidence: 99%
“…Recently, metal oxides without solubility in most organic solvents have been extensively explored as excellent additives to combine with sulfur for improving the performance of Li–S batteries . Metal oxides with an oxygen anion in their structure provide a strong polar surface, which can afford abundant polar active sites for entrapment of polysulfide.…”
Section: Metal Oxides As Sulfur Hosts For Li–s Batteriesmentioning
confidence: 99%